2021
DOI: 10.3390/molecules26020331
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity and Anti-Adipogenic Effects of Chitosan Oligosaccharide (GO2KA1) in SD Rats and in 3T3-L1 Preadipocytes Models

Abstract: Excess body weight is a major risk factor for type 2 diabetes (T2D) and associated metabolic complications, and weight loss has been shown to improve glycemic control and decrease morbidity and mortality in T2D patients. Weight-loss strategies using dietary interventions produce a significant decrease in diabetes-related metabolic disturbance. We have previously reported that the supplementation of low molecular chitosan oligosaccharide (GO2KA1) significantly inhibited blood glucose levels in both animals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Recently, the same team evaluated the antiobesity effect of COS on lipid accumulation and adipogenic gene expression with 3T3-L1 adipocytes and an SD rat model, respectively. The findings suggested that COS may prevent diet-induced weight gain and that the antiobesity effect is mediated partially via inhibiting adipogenesis and increasing adiponectin levels [ 77 ]. Obesity, the most common chronic metabolic disease, has been proved to induce low-grade inflammation [ 78 ].…”
Section: Biological Activities Of Chitosan and Cosmentioning
confidence: 99%
“…Recently, the same team evaluated the antiobesity effect of COS on lipid accumulation and adipogenic gene expression with 3T3-L1 adipocytes and an SD rat model, respectively. The findings suggested that COS may prevent diet-induced weight gain and that the antiobesity effect is mediated partially via inhibiting adipogenesis and increasing adiponectin levels [ 77 ]. Obesity, the most common chronic metabolic disease, has been proved to induce low-grade inflammation [ 78 ].…”
Section: Biological Activities Of Chitosan and Cosmentioning
confidence: 99%
“…It has been reported by many studies that oligosaccharides lower blood glucose levels with different modes of action speculated among the types of oligosaccharides such as immune response [ 22 ]. In order to focus on functional food ingredients that could be safely taken by patients in their diet, we chose to add oligosaccharides into a murine-certified diet based on their therapeutic effects on metabolic syndrome and capacity to improve intestinal bacterial flora [ 12 , 23 , 24 ]. As expected, milk-derived oligosaccharides alleviated blood and urine glucose levels and restored the integrality of pancreatic islets of Langerhans in TSOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…3T3-L1 cells (ATCCV ® CL-173TM) were used below passage 12. 3T3-L1 preadipocytes were propagated and cultured in DMEM medium supplemented with 10% BCS and 1% P/S until confluent and maintained for additional 2 days and differentiated as reported previously [ 26 ] with or without BEE.…”
Section: Methodsmentioning
confidence: 99%